PRE-TERTIARY TEACHER PROFESSIONAL DEVELOPMENT AND MANAGEMENT IN GHANA - Kwabena , Agyei Mensah; Ofori-Ansah, Nana Yaa; Amoah, Emmanuel Boateng (Top Educational Review Journal (TERJ), 2023)
Teachers in the Greater Accra Region regarding continuous professional development (CPD) programs. Employing a descriptive survey design, the study utilized Google Forms to construct a survey, disseminating the link within a WhatsApp group comprising 141 teachers from 63 basic schools in the Greater Accra Region, purposively sampled for participation. The response rate was 100%, with all 141 teachers providing input. The study uncovered diverse reactions among teachers concerning CPD programs/activities in Ghana. Notably effective were programs such as "Cluster/School-Based INSET, ICT Integration in Teaching and Learning, Peer Class Observation, Classroom Management, and Subject Content and Methodology Professional Development," tailored to teachers' needs. Conversely, activities like "Educational Leadership and School Management, Education of persons with Special Needs, Micro Teaching, and Social Dialogue" were perceived as ineffective due to misalignment with teachers' needs. The study's findings offer valuable insights for policymakers, educational administrators, and all stakeholders in education. The conclusions and recommendations drawn from this study contribute to enhancing the design and implementation of CPD programs for pre-tertiary teachers in Ghana